Application of the Order-Picking and Self-Organizing Maps Models to Optimize the Supply Chain: A Review of the Literature - López-Santos, Irving (IGI-Global, 2019)
At present, the management systems of companies and Industry 4.0 are closely linked. However, technologies that promise to drastically help the efficiency of operations are not implemented in production floors and specifically in warehouses. This chapter shows a methodology of bibliographic search that determines the most recent optimization algorithms and with greater occurrence within the scientific literature. Editorials and scientific journals are also taken into account. The information is analyzed and shown in the conclusion part of the work. The conclusions indicate the hybrid algorithms with greater publication, their characteristics, the different types of metrics used for the implementation of optimization systems in production environments, and the secondary support algorithms used to cover the performance weaknesses of the main algorithms.